PENGARUH BEBERAPA FAKTOR PENGOLAHAN TERHADAP SIFAT ARANG AKTIF - R Sudradjat (Jurnal Penelitian Hasil Hutan, 1985)
Variables used in this investigation are wood species (Jelutung and keruing), carbonization temperatures (400°C and 500°C) and activators (CaCl2, MgCl2 and ZnCl2). The parameters observed were yield, moisture content, ash content, iodine and benzene adsorption. This investigation reveals that the highest yield obtained from keruing wood, CpCl2 activator at carbonization temperature of 400°C. The lowest moisture content charcoal obtained by using processing temperature of 500°C. Jelutung wood with MgCl2 activator had the lowest moisture content compared to that of ZnCl2 activator. The highest iodine adsorption obtained when using ZnCl2 activator and carbonization temperature of 500°C (for keruing wood). It was found that high benzene vapor adsorption charcoal could be produced by using ZnCl2 activator, carbonization temperature 500°C and Jelutung wood as raw material.Sunbury, H.M. (1923). The destructive distillation of wood. Ben Brother, Ltd., London.Hartoyo (1975). Arang aktif, pembuatan dan penggunaan. Kehutanan Indonesia.Sudradjat Prawirakusuma dan Tjipto Utomo (1972). Pembuatan Arang Aktif. Lembaga Kimia Nasional. LIPI Bandung.